Understanding Loyalty in the Aviation Sector: The Mediating Role of Perceived Value between Brand Equity and Loyalty - Okan, Serdar (International Review of Management and Marketing, 2026)
This research examines the mediating role of perceived value in the relationship between brand equity and passenger loyalty, focusing on Turkish Airlines. Data were gathered from 569 passengers of Turkish Airlines and were analyzed by using EFA in SPSS and CFA in SmartPLS. The results indicate that brand equity significantly has an indirect impact on passenger loyalty (β = 0.112, p = 0.011). In addition, although brand equity has a positive effect on perceived value (β = 0.240, p < 0.001), perceived value also has a positive effect on loyalty (β = 0.493, p < 0.001). The results also indicate that perceived value partially mediates the effect of brand equity on loyalty (β = 0.118, p < 0.001). Such findings imply that post-flight communication with the company, passengers’ feedback opportunities and efficient service problem resolution might result in an increase of perceived value fostering customer loyalty. There appears to be a significant underestimation of the importance of the direct effect and of its impact on the indirect effects of brand equity. This study bridges the research gap by analyzing perceived value as a mediator between brand equity and loyalty, focusing on Turkish Airlines.